Responsibility for racism in the everyday talk of secondary students. Issue 1 (2nd January 2017) - Halse, Christine
ABSTRACT: This article examines the attributions of responsibility for racism in the everyday talk of secondary school students. It draws on focus groups with a cross section of students from different ethnic backgrounds in three, very different, secondary schools. In these focus groups, students deploy six different, sometimes contradictory, racialised discourses. Each discourse attributes responsibility for racism in very different ways that testify to the immanence of the past in the present and students' positioning in specific social and political conditions. In all but one instance, these discourses work to dismiss, deny and/or deflect responsibility for racism by averting responsibility from the self to other individuals, groups or entities. The empirical data, it is argued, show that the individualisation of responsibility for racism has not seeped its way into students' race-thinking. This testifies to the persistence of race-thinking, the difficult challenge of finding non-racist ways of being in the world, and cautions against assuming that responsibilisation is a universal descriptor of all contemporary social relations.